Radiation Awareness among Secondary School Students in Perak, Malaysia - Maulana, Mohd; Nadia, Izza; ., Othman; Shakila, Nur; Syahidatul Akmar, Safian; ., Ramli; ., Zuraida; ., Sahraduin; ., Rasida; ., Yasim; ., Rosshasni (International Journal of Engineering and Technology, 2018)
Currently, the number of student enrolment for Radiography programme in Universiti Kuala Lumpur â€“ Royal College of Medicine Perak is the lowest compared to other programmes. Hence, this study is done to determine studentsâ€™ tendency to further their study in radiography or related programme and determine the radiation awareness among the secondary school students. A survey was conducted on n=429 form four secondary school students under national standard curriculum. 75.5% of the data were collected from seven government secondary schools in Perak, while the remaining were collected from visitors of our institution. The result shows the average score of basic knowledge regarding radiation with mean score of 59.53% and standard deviation of 18.89%. Meanwhile, printed reading materials is the highest type of information source and video game is the lowest with 25.9% and 0.2% respectively. 46.2% claimed that they are fear to radiation and all of them agreed that the radiation disaster incidences was their main reason. 92.3% claimed that they will seek for their parentsâ€™ opinion and 17.5% claimed to follow their parentsâ€™ choice with regard to the choice of future career while 50.8% claimed that they may continue their higher education in radiography or related programme. Result also showed that fear to radiation effects the studentsâ€™ tendency to choose radiography or related programme as their choice [p<0.05]. It can be concluded that the radiation awareness among secondary school students in this study is assumed as average and the tendency to further study in radiography or related programme is quite low mainly due to their fear to radiation disaster incidence.Â Â